If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(n) = -92 + -25(n + -1) Multiply f * n fn = -92 + -25(n + -1) Reorder the terms: fn = -92 + -25(-1 + n) fn = -92 + (-1 * -25 + n * -25) fn = -92 + (25 + -25n) Combine like terms: -92 + 25 = -67 fn = -67 + -25n Solving fn = -67 + -25n Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'n'. f = -67n-1 + -25 Simplifying f = -67n-1 + -25 Reorder the terms: f = -25 + -67n-1
| 4sin^2-2cosx+1=0 | | 3t^3+12t^2+12t=0 | | (3x-21)(x+5)=0 | | 20+20*0= | | 6x-0=3-3x | | 3x^3+24x=-27x^2 | | 4-4b+2b=-2-2(1-b) | | x=4y^6 | | 20z=1500 | | 10z=1800 | | 20z=1000 | | 20z=2100 | | 36X-4.5X^2=0 | | ln(3-2x)=11 | | 7x^3+14x^2= | | 8-a=24 | | x+9.3=32.7 | | x+9.3=31.7 | | a-12=-4 | | 8x^2+59x=-21 | | 128x^6=0 | | 3.9x+2.1=13.8 | | 36x-72=9 | | 7x+35=42 | | 7x+35=41 | | F(x)=(3x+3)(-2x+6) | | Fx=2x^2+4x+2 | | 0.5=a(3.5)2+b(3.5) | | Fx=2x^2+12x+17 | | 0.5=a(3.5)+b | | 16x^2-48x+3=35 | | 16x-64=16 |